THE INFLUENCE OF ENTREPRENEURSHIP KNOWLEDGE AND INNOVATION ON THE CONTINUITY OF FOOD AND BEVERAGE MANAGEMENT BUSINESS IN BANDUNG DISTRICT - Suherman Suherman (Jurnal Scientia, 2023)
The goal to be achieved in this study is to determine the effect of entrepreneurial knowledge and innovation on the sustainability of food and beverage management businesses in Bandung regency. The method used in this research is explanatory research. The population of this study are printing entrepreneurs in the Medan City Region, totaling 476 food and beverage management entrepreneurs in Bandung Regency, where the sampling technique in this study uses the Slovin formula so that the research sample is 127. The results obtained simultaneously and partially Entrepreneurial Knowledge and Entrepreneur Innovation variables have a significant influence on the sustainability of the Food and Beverage Management business variable in Bandung Regency. To overcome the changes that exist, it is better for Food and Beverage business entrepreneurs to increase their knowledge about digital so that sales can not only be made through offline sales, but can also be made online, so that consumers in all districts and cities of Bandung can find out, so that food and beverage management business products drink can be known by many people.